Issues limiting the evaluation of post implemented enterprise architecture - Rouhani, Babak Darvish; Nikpay, Fatemeh; Ahmad, Rodina (Institute of Advanced Engineering and Science, 2019)
Evaluation in enterprise architecture (EA) project is crucial to provide comprehensive information of the developed EA artefacts. It may assist in accurate evaluation of implemented Information Systems (ISs) in order to realize the achievement of EA’s goals and support EA decision makers. This research aims to identify and elaborate the existing issues of EA evaluation models. One of the crucial identified issues is to understand, capture and represent core aspects of EA artefacts. Most existing evaluation models do not provide structured approach which cover comprehensive aspect of EA implementation and some do not provide good practices to be applied. Hence, this research intends to cover the gap by exploring critical issues in EA implementation evaluation and elaborating main shortcomings of the reviewed EA models and methods through a systematic literature review. Copyright © 2019 Institute of Advanced Engineering and Science. All rights reserved.